Toni Morrison and motherhood : a politics of the heart - O'Reilly, Andrea, 1961- (State University of New York Press, 2004)
Motherhood, in Morrison's view, is fundamentally an act of resistance, essential to black women's fight against racism & sexism, & their ability to achieve well-being for themselves & their culture. Andrea O'Reilly explores this theory.